Clonal redemption of B cells in cancer - McCaw, Tyler R.; Lofftus, Serena Y.; Crompton, Joseph G. (Frontiers in Immunology, 2023)
Potentially self-reactive B cells constitute a large portion of the peripheral B cell repertoire in both mice and humans. Maintenance of autoreactive B cell populations could conceivably be detrimental to the host but their conservation throughout evolution suggests performance of a critical and beneficial immune function. We discuss herein how the process of clonal redemption may provide insight to preservation of an autoreactive B cell pool in the context of infection and autoimmunity. Clonal redemption refers to additional recombination or hypermutation events decreasing affinity for self-antigen, while increasing affinity for foreign antigens. We then review findings in murine models and human patients to consider whether clonal redemption may be able to provide tumor antigen-specific B cells and how this may or may not predispose patients to autoimmunity.